Pengelolaan Budi daya Rumput Laut dengan Pendekatan Sosial-Ekonomi dan Ekologi di Pulau Pari - Neksidin Neksidin; Triyono Triyono; Sri Murtini (Institut Pertanian Bogor, 2024)
Seaweed plays an essential role in the people's economy in Pari Island because its cultivation has been the main livelihood for a long time. Currently, seaweed cultivation activities are no longer found, possibly due to tourism activities that directly degrade the cultivation activities. The purpose of this study is to evaluate the status of sustainability and determine the strategy of cultivation management in 5 aspects: ecological, social, economic, institutional, and infrastructure. Data were collected from primary and secondary sources related to socio-ecology in Pari Island. The assessment of the level of sustainability in each dimension was carried out using multidimensional scaling analysis, and a fairly sustainable average suitability value was obtained, namely the infrastructure (73.37), institutional (71.24), ecological (62.48), and economics (62.16). Meanwhile, the dimension with a very suitable sustainability value is the social dimension, with a value of 76.33, meaning that it is very suitable. Overall, the sustainability of seaweed cultivation, if viewed from several dimensions, shows the level of suitability of cultivation, both in terms of infrastructure, institutions, ecology, and economics. However, several dimensions, such as economic and ecological dimensions, must still be considered and continue to be encouraged so that sustainability can be achieved in all dimensions. Keywords: cultivation, management, Pari Island, seaweed, socio-ecology